Estimation of vertical center of gravity position by underwater motion-capture system with small number of markers during swimming - Washino, S.; Mankyu, H.; Yoshitake, Y. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
The purpose of this study was to test if 1) the vertical centre of gravity (COG) position of a swimmer during front crawl swimming is affected by their lung volume level and 2) the COG can be accurately estimated by the position of the trunk segment. Six well-trained male swimmers (21.3 ± 1.7 yrs, 100m-best time: 55.7 ± 3.5 s; mean ± SD) performed front crawl swimming with three different sustained lung volume levels, i.e., maximal inspiration (MAX), maximal expiration (MIN), and intermediate between these (MID). The participants were instructed to swim at the same submaximal-speed across trials for 15m. Twenty-five reflective markers were attached to the participant`s body according to standard procedures and 3-D positions of these were recorded at 100frames/s using the underwater motion-capture system. Vertical position for the xiphoid process (XP), the medio-lateral centre between left and right greater trochanters (GTc), the centre between XP and GTc (XP-GTc), and the vertical COG position were calculated and averaged for one-stroke cycle period. These validities of measures in estimating vertical COG position were assessed using intra-class correlation coefficient (ICC) and Bland-Altman plot across all trials. There was no difference in velocity between swimming with different lung volumes (p > 0.05). The COG position from the water surface was lower in MIN compared with that in MAX and MID (p < 0.05). The COG position in MID tended to be lower than that in MAX (p = 0.056). When collapsed across lung volume levels, ICC was 0.870 for XP, 0.977 for GTc, and 0.977 for XP-GTc (all p < 0.001). The Bland-Altman plot revealed that there was a proportional error only between COG and GTc (p < 0.001). These results indicate that 1) lung volume is an important determinant of vertical COG position of a swimmer during front crawl swimming and 2) vertical COG position can be accurately estimated using markers placed on the XP and GT. The latter further suggests that the vertical COG position can be estimated without a number of the reflective markers which should increase unwanted extra-water resistance.